Impact of floor covering on wheelchair rugby players: analysis of rolling performance - Vigié, O.; Faupin, A.; Ngo, M-A.; Fauvet, C.; Pradon, D. (Frontiers in Sports and Active Living, 2024)
Introduction Despite the increased interest in indoor wheelchair sports in many countries, research on the effect of floor coverings on sports performance is limited. Currently, there are no specific guidelines for covering characteristics for wheelchair sports, whether for competitive or recreational purposes. This study aimed to determine the impact of floor coverings on the biomechanical parameters of manual wheelchair propulsion for wheelchair rugby practice. Methods Ten wheelchair rugby players performed 6 maximum-velocity sprints over 20 meters, with a 20-second recovery time between sprints, on 3 different coverings, using their personal sports wheelchairs. The coverings were: wood parquet, Gerflor TX System Endurance®, and a plastic synthetic covering (balatum). Performance and propulsion technique variables were collected using inertial measurement units (265 Hz, Kinvent, France). Additionally, rolling resistance quantification tests were conducted on each covering. Results Rolling resistance was lowest on the wood parquet, with an average value of 3.98 ± 0.97 N. Best sprint performance was achieved on the wood parquet. The fatigue index on the parquet was significantly lower than on the balatum (p < 0.05). Discussion Our results highlight that floor surface influences both performance and propulsion technique variables. Therefore, we recommend performing wheelchair rugby training on wood parquet to optimize performance. It is also important to consider the impact of different coverings on sprint performance when organizing player rotations to maintain a high level of competition during tournaments.